TEKNIK PEMBUATAN SUSU KEDELAI - Juliawati Juliawati; Ilya Puryani; Tasliati Tasliati; Sulaiman Sulaiman; Jauhari Jauhari (COVIT (Community Service of Health), 2022)
This community service activity (PPM) is carried out to increase public awareness of the importance of milk for fulfilling nutrition in realizing health, and the purpose of consuming milk, including soy milk, especially for school children at the elementary level. Soy milk is a healthy drink, rich in protein and fiber and natural, made from soybeans with a high protein content. This activity was carried out at SD Negri Pertiwi Lambarot, Want Jaya District, Aceh Besar District with a target number of 100 participants who are the board of teachers and students of Pertiwi Elementary School with participants aged 9-60 years. The presentation of this community activity was carried out by a lecturer at the Faculty of Agriculture, University of Iskandar Muda, using lecture methods and demonstrations on the production of soy milk. The steps for this activity are: preparing target locations, counseling materials and participants directly practicing the technique of making soy milk as a healthy drink. The results of the observations showed that Pertiwi Lambarot elementary school students preferred cow's milk for consumption rather than soy milk, soy milk was consumed more by adults. Keywords : elementary school students, soybean milk, and manufacturing techniques